THE INFLUENCE OF ENVIRONMENT MANAGEMENT ACCOUNTING, BUSINESS STRATEGY TO COMPANY ENVIRONMENT PERFORMANCE - Irma Paramita Sofia; Hariyanti, Viky (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Banten Province is one of the areas that can be said to be new where there are many new industries in various fields. Although the industrial area in Banten is still relatively new, there have been many cases of environmental damage caused by industrial waste. The number of cases of industrial waste is one source of environmental damage, so in addition to thinking about economic benefits, economic activity actors should also be more responsible for the environment. With this case, many industrial companies put aside the negative and positive impacts that the company may receive in the future. This study aims to analyze environmental management accounting which refers to environmental costs and business strategy which refers to the differentiation strategy on the company's environmental performance. The sample used in this study is industrial sector manufacturing companies listed on the Indonesia Stock Exchange and participating in the PROPER Program in the Banten region with a period of 5 periods. The type of data used is secondary data from www.idx.co.id. The method used to analyze this research is a quantitative method.